2000
DOI: 10.1038/sj.ijo.0801246
|View full text |Cite
|
Sign up to set email alerts
|

Underreporting of energy intake in four populations of African origin

Abstract: OBJECTIVE: To investigate the frequency of dietary underreporting in four African populations in different geographic and cultural settings. SUBJECTS: Seven-hundred and forty three men and women from rural Cameroon, 1042 men and women from urban Cameroon, 857 men and women from Jamaica and 243 male and female African Caribbeans from the UK. Subjects who reported dieting or weight control were excluded. MEASUREMENTS: Habitual dietary intake was estimated with a quantitative food frequency questionnaire, develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
33
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 12 publications
8
33
0
Order By: Relevance
“…Our earlier report 18 showed that the prevalence of underreporting was lowest in rural Cameroon, somewhat higher in urban Cameroon and Jamaica and highest in the UK, suggesting trends in cultural influences on obesity.…”
Section: Non-dietary Factorsmentioning
confidence: 80%
See 1 more Smart Citation
“…Our earlier report 18 showed that the prevalence of underreporting was lowest in rural Cameroon, somewhat higher in urban Cameroon and Jamaica and highest in the UK, suggesting trends in cultural influences on obesity.…”
Section: Non-dietary Factorsmentioning
confidence: 80%
“…In crosssectional studies weight status may influence intakes and obscure any relationship of dietary contribution to weight outcomes. In spite of the care taken to eliminate underand over-reporters, our data may also be subject to methodological bias, such as the ability to estimate diet 11 , as previously discussed 18 . An unexpected finding was the association of higher protein intake with overweight.…”
Section: Diet and Excess Weightmentioning
confidence: 97%
“…In an Irish study (Kilkenny Health Project), reported energy intake from an FFQ below a cut-off of 1.27 identified 53% of subjects as underreporters 25 . Another FFQ administered in the UK evaluated close to 39% of men and 28% of women as underreporters 26 . It must be noted that dietary underreporting is not confined to FFQs, but occurs with all dietary assessment methods, indicating a possibly consistent aberrant behaviour when nutritional evaluation is performed 3,7 .…”
Section: Discussionmentioning
confidence: 99%
“…Participants were categorised by age group (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) 21 . The PAL values were 1.55, 1.78 and 2.10 for men, and 1.56, 1.64 and 1.82 for women.…”
Section: Assessment Of Lifestyle Variablesmentioning
confidence: 99%
“…The cut-off level for defining under-reporting depends on the physical activity level of the population. We collected data on activity and energy expenditure based on Lipid Research Clinic (LRC) questionnaire, 24 but, because it had not been validated for our society, the results were unreliable so under-reporters were identified by cut-off value of energy intake divided by basal metabolism rate estimated using Harris and Benedict's equation 25 of less than 1.15 for adults 26 and 1.06 27 for children and adolescents. These cut-off points have been used for subjects with sedentary to average physical activity levels in previous reports.…”
Section: Measurementsmentioning
confidence: 99%